PET myocardial perfusion quantification: anatomy of a spreading functional technique - Juarez-Orozco LE; Cruz-Mendoza JR; Guinto-Nishimura GY; Walls-Laguarda L; Casares-Echeverria LJ; Meave-Gonzalez A; Knuuti J; Alexanderson E (SPRINGER-VERLAG ITALIA SRL, 2025)
Purpose To summarize the physical principles, imaging method, available tools for and the clinical value of quantitative perfusion evaluation with cardiac PET as well as future aims in the field in a narrative review.Results Cardiac positron-emission tomography (PET) currently constitutes the reference standard for non-invasive quantitative evaluation of myocardial blood flow. This added modality provides useful information beyond standard semi-quantitative myocardial perfusion evaluation. A description of how the different phases of PET studies are interpreted is provided, as well as a short depiction of the most commonly used radiotracers and the main characteristics affecting their clinical utility. The diagnostic and prognostic utility concerning myocardial perfusion quantified in absolute terms is discussed and the additional contribution of the increasingly spread hybrid equipment is summarized.Conclusion PET myocardial perfusion represents an excellent noninvasive technique for the evaluation of known or suspected ischemic heart disease, and its clinical application should widen in the near future. The clinical value of PET quantitative perfusion is expected to improve patient outcomes and optimize therapeutic decisions, which constitute key elements for the future of cardiovascular medicine.